Management of environmental management for the sustainable development of public and private companies in the Piura region, Peru (Revista Innova Educación, 2021)
Goal. Demonstrate how the management of systemic environmental management contributes to the growth of sustainable development in small and medium-sized companies in the public and private sectors in the Piura region. Material and method. This work was carried out under the deductive hypothetical paradigm, of a basic substantive type and of transversal correlational design. The study was made up of 159 managers and administrators of the entities mentioned. The survey technique was applied through questionnaires that comprised the dimensions of 1) personal domain, 2) mental models, 3) continuous learning and shared vision, 4) systemic thinking. While the methodology was used, the Chi-Square analysis problem was established to establish the association levels based on the analysis of dichotomous contingency tables. Results. It was determined that it exists for the dimensions: personal domain, mental models, continuous learning and shared vision and systemic thinking of a chi-cuadrada of 31,196, 40,789,51,078 and 38,330, as they turned out to be larger than the chi-cuadrado tabulate the criticism, for so much so, there is a high degree of significant relationship between the dimensions with the management of the systemic environmental manager. Conclusion. There is a high degree of correlation between the management of systemic environmental management and the increase in sustainable development.
Keywords: Sustainable development; management; environmental management; medium business; small business